2017
DOI: 10.1111/jjns.12178
|View full text |Cite
|
Sign up to set email alerts
|

Social capital in Japan: What characteristics do public health nurses see in their communities?

Abstract: The results contribute to an understanding of social capital in the context of public health nursing activities and further research on social capital. It also is discussed how social capital can be incorporated into public health nursing activities in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Although no previous studies have investigated the association between social capital and ART use, it is possible to identify several reasons for this association. First, individuals with high social capital are more likely to receive medical care; many studies have investigated the relationship between social capital and healthcare-seeking behavior and outcomes ( Chuang et al, 2015 ; Derose & Varda, 2009 ; Honda et al, 2018 ; Inoue et al, 2020 ; Rodgers et al, 2019 ; Santoso et al, 2020 ). A recent survey of 8770 employees aged 18–70 years found that both men and women with low workplace social capital had a significantly higher risk of not seeking medical care than those with high workplace social capital group ( Inoue et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although no previous studies have investigated the association between social capital and ART use, it is possible to identify several reasons for this association. First, individuals with high social capital are more likely to receive medical care; many studies have investigated the relationship between social capital and healthcare-seeking behavior and outcomes ( Chuang et al, 2015 ; Derose & Varda, 2009 ; Honda et al, 2018 ; Inoue et al, 2020 ; Rodgers et al, 2019 ; Santoso et al, 2020 ). A recent survey of 8770 employees aged 18–70 years found that both men and women with low workplace social capital had a significantly higher risk of not seeking medical care than those with high workplace social capital group ( Inoue et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These messages were prepared based on evidence from previous Japanese studies [12,22,23]. The public gain-framed message described the advantage of engagement in collective social participation activities for community connectedness and the security of residents in the community, based on evidence from previous Japanese studies [24][25][26].…”
Section: Framed Messages and Allocationmentioning
confidence: 99%